1972
DOI: 10.1136/jnnp.35.3.414
|View full text |Cite
|
Sign up to set email alerts
|

Stuttering: an investigation into cerebral dominance for speech

Abstract: SUMMARY Over the past decade research has suggested that stutterers have bilateral cerebral motor or auditory speech areas. Three typical adult stutterers showed normal unilateral left cerebral dominance for speech on the intracarotid sodium amylobarbitone (amytal) test, but one 'dysphatic' stutterer had bilateral cortical speech representation. The latter is a very rare finding in right handed individuals and presumably is a consequence of the head injury induced aphasia that preceded the onset of stuttering.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
2

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 17 publications
(15 reference statements)
0
14
1
2
Order By: Relevance
“…Another study, however, found that speech was disrupted on the right side only in a patient who had previously had brain injury and aphasia as well as stuttering. The other persons with idiopathic stuttering, only had speech disruption with amytal infusion on the left side, similar to normal (Andrews, Quinn, & Sorby, 1972). Similarly, a study of three PWS without brain injury found all had left hemisphere dominance for speech on WADA testing (Luessenhop, Boggs, LaBorwit, & Walle, 1973).…”
Section: The Rapid Interplay Between Multiple Systems Required For Flmentioning
confidence: 89%
“…Another study, however, found that speech was disrupted on the right side only in a patient who had previously had brain injury and aphasia as well as stuttering. The other persons with idiopathic stuttering, only had speech disruption with amytal infusion on the left side, similar to normal (Andrews, Quinn, & Sorby, 1972). Similarly, a study of three PWS without brain injury found all had left hemisphere dominance for speech on WADA testing (Luessenhop, Boggs, LaBorwit, & Walle, 1973).…”
Section: The Rapid Interplay Between Multiple Systems Required For Flmentioning
confidence: 89%
“…It is consistent with the long-standing suggestion that right hemisphere functional lateralization may be a compensatory mechanism (Braun et al, 1997) that prompts a neuroplastic reorganization of language activity. Other researchers have proposed that right hemisphere involvement interferes with speech fluency pathways and may be a cause of stuttering (Andrews, Quinn, & Sorby, 1972; Webster, 1990). “In the adult system it may be difficult to distinguish between mechanisms responsible for stuttering and those developed to compensate” (Ludlow, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Stuttering is a common condition, especially the developmental form, which can have a prevalence of 1% in the adult population (Andrews, Quinn, & Sorby, 1972). Devel-opmental stuttering almost always begins in childhood or early adolescence, and it is much more common in males.…”
Section: Discussionmentioning
confidence: 99%